A1.30 A key role of S100A9 in the pathogenesis of psoriatic arthritis in TTP/S100 deficient mice. (24th February 2016) - Fröhling, M; Vogl, T; Loser, K; Paruzel, P; Blackshear, PJ; Stumpo, DJ; Roth, J; Pap, T; Stratis, A
Abstract : Background and objectives: Psoriatic-Arthritis (PsA) is a type of inflammatory chronic arthritis with a seronegative spondyloarthropathy and associated psoriasis. The S100 calcium-binding molecules S100A8 and S100A9, known as damage-associated molecular pattern molecules (DAMP), are highly increased during many inflammatory disorders and their expression correlates with the severity of disease. S100A8 and S100A9 are expressed in low levels in normal epidermis, but are highly expressed in psoriasis. Interestingly a high expression of epidermal S100A8/S100A9 is also an early marker found in patients suffering from systemic onset of juvenile idiopathic arthritis, which has led us to investigate the role of DAMPs under chronic inflammatory conditions. Material and methods: To analyse the role S100A8 and S100A9 have during inflammation, we crossed S100A9-deficient mice withTTP (tristetraprolin)-deficient mice as a systemic inflammatory model featuring high levels of TNF. Disease progression in TTP-/- x S100A9-/- mice was analysed by immunostaining, immunhistochemistry and the adapted PASI-score. RNA was extracted from snap-frozen mouse tissue for Real-time quantitative PCR analysis. To neutralise TNF in TTP-/- x S100A9-/- mice we used an aTNF-inhibitor monoclonal antibody already in clinical use for therapy of arthritis and psoriasis. To measure altered protein levels we used Western blot analysis. Results: The loss of S100A9 in TTP-deficient mice leads to highly elevated amounts of S100A8 in the epidermis and furthermore to a severe psoriasis-like phenotype at postnatal day 8. The expression of other effector molecules in the TTP -/- /S100A9 -/- mice know to be involved in the pathogenesis of psoriasis, incuding IL-17, IL-23 and IL-22 is markedly increased compared to TTP -/- mice. Treatment withanti-TNF preventedthe mice from developing the psoriatic phenotype, indicating that the psoriasis-like skin disease of TTP -/- /S100A9 -/- mice is tumour necrosis factor (TNF) dependent. Conclusions: Our results demonstrate that under inflammatory conditions, S100A9 is essential for the regulation of inflammation, suggesting that S100A9 released from epidermal cells may act not only as a systemic danger signal that is involved in the initiation of inflammatory disorders like psoriasis and arthritis, but may also have a homeostatic anti-inflammatory function in the skin.